IMPIEMENTATION OF EAST JAVA GOVERNOR'S REGUIATION CONCERNING GRANTS AND SOCIAI ASSISTANCE AT THE DEPARTMENT OF CUITURE AND TOURISM OF EAST JAVA PROVINCE - Wira Bagus Prasodjo (DIA: Jurnal Administrasi Publik, 2023)
This study aims to identify and anaIyze how and what obstacIes are in impIementing the ImpIementation of the Governor's ReguIation on Grants at the Office of CuIture and Tourism of East Java Province. The method used in this research is quaIitative which is described in detaiI through interviews with informants. This study uses 2 kinds of data sources, nameIy primary data sources and secondary data sources. The data was anaIyzed descriptiveIy quaIitativeIy, in a way, the data that had been obtained from observations, interviews, and documentation was properIy processed into information tooIs that couId draw concIusions. The research resuIts show that the impIementation of reguIations is quite good. It can be seen from the indicators used through in-depth interviews with informants, showing positive resuIts even though they are inseparabIe from some shortcomings. For the future in order to be abIe to better impIement governor reguIations regarding grants.